Evaluation of Earth Observing-1 (EO1) data for lithological and hydrothermal alteration mapping: a case study from Urumieh-Dokhtar Volcanic Belt, SE Iran - Pour, Amin Beiranvand (Indian Society of Remote Sensing, 2015)
This study evaluates the capability of Advanced Land Imager (ALI) and Hyperion Earth Observing-1 (EO1) data for lithological and hydrothermal alteration mapping. Several image processing methods were applied to ALI and Hyperion images covering the Meiduk and Sar Cheshmeh porphyry copper mining districts, SE Iran. Feature-oriented principal components selection, developed band ratio and minimum noise fraction methods were able to yield spectral information for enhancing the hydrothermally altered rocks and lithological units at regional scale using ALI data. Mixture-tuned matched-filtering method discriminated hydrothermal alteration areas from surrounding rock units using shortwave infrared bands of ALI. Analytical imaging and geophysics (AIG)-developed hyperspectral analysis processing methods were applied to the visible and near infrared and shortwave infrared bands of Hyperion for mapping iron oxide/hydroxide minerals and clay mineral assemblages at district scale. Supergene altered areas consisting of iron oxide/hydroxide minerals such as hematite, limonite, jarosite and goethite were detected using visible and near infrared bands of Hyperion. Phyllic, advanced argillic and propylitic alteration zones associated with porphyry copper mineralization were discriminated using shortwave infrared bands of Hyperion. The achievements of this investigation indicate considerable implications for geologists to use Earth Observing-1 data for porphyry copper and epithermal gold exploration.